Green Port Strategies for Indonesian Maritime Logistics: A Systematic Review of Mining Barging and General Cargo - Samuel Darwisman; Marcellus Jayawibawa; Handy Bugiman; Ahmad Fajar Asrori; Agus Dian Hermawan; Zaenal Abidin (Dinasti Publisher, 2025)
Indonesia's maritime logistics, particularly its vital mining barging and general cargo sectors, face a critical tension between economic growth and environmental sustainability. While green port strategies are a national priority, a holistic synthesis connecting global principles to Indonesia’s unique archipelagic context is absent. This study bridges that gap via a systematic literature review, adhering to PRISMA guidelines. A rigorous analysis of 37 high-quality articles (2015-2025), appraised via the CASP checklist, reveals a persistent